ESG: Its Threshold Effect on Asian Energy Company Profitability - Lee, Chee Loong; Ming, Kelvin Lee Yong; Yee, Lee Chin (International Journal of Energy Economics and Policy, 2025)
The impact of Environmental, Social, and Governance (ESG) factors on corporate financial performance remains a subject of ongoing debate among researchers. This study investigates the disaggregated components of ESG and their threshold effects on the profitability of Asian energy companies. Employing dynamic threshold panel regression, we find that the Environmental pillar score (E) enhances profitability when maintained below specific thresholds, while the social pillar score (S) shows profitability benefits when exceeding certain thresholds. Surpassing these thresholds, however, may either diminish or further enhance profitability, underscoring the dual risks and benefits associated with ESG practices. These findings reveal the profitability-enhancing potential of ESG scores while emphasizing the importance for energy companies to strategically manage their ESG components. Such careful management can mitigate the risk of diminishing returns and simultaneously improve financial performance through enhanced reputation and operational efficiency.